2016
DOI: 10.1039/c6ra05457a
|View full text |Cite
|
Sign up to set email alerts
|

Application of spent mushroom (Lentinula edodes) substrate and acclimated sewage sludge on the bioremediation of polycyclic aromatic hydrocarbon polluted soil

Abstract: A novel technology for remediation and improvement of soil was provided along with a new approach for waste recycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The addition of nitrogen-rich nutrients (biostimulation) and potentially viable microbes (bioaugmentation) through organic materials application to soils are two effective approaches for the bioremediation of PAH-contaminated soils (Wang et al, 2016). The results in the present study showed that contact time influenced the development of catabolic activity as defined by decreases in the length of the lag phases and increases in the rates and extents of mineralization of 14 C-phenanthrene in amended soils.…”
Section: Organic Amendment Ratios On 14 C-phenanthrene Mineralizationmentioning
confidence: 60%
“…The addition of nitrogen-rich nutrients (biostimulation) and potentially viable microbes (bioaugmentation) through organic materials application to soils are two effective approaches for the bioremediation of PAH-contaminated soils (Wang et al, 2016). The results in the present study showed that contact time influenced the development of catabolic activity as defined by decreases in the length of the lag phases and increases in the rates and extents of mineralization of 14 C-phenanthrene in amended soils.…”
Section: Organic Amendment Ratios On 14 C-phenanthrene Mineralizationmentioning
confidence: 60%
“…White rot fungi, frequently referred to as lignin‐degrading fungus, release ligninolytic enzymes with quite a minimal substrate specificity, for example L. edodes and Pleurotus pulmonarius release Mn‐peroxidase, laccase, versatile peroxidase and lignin peroxidase, which are enzymes capable of degrading a wide range of structurally related organic contaminants, including dioxins, chlorophenols, dyes, phenols, pesticides, polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls and solvents 50 . The SMS still had a high concentration of these enzymes, along with persistent mycelia capable of secreting these extracellular enzymes.…”
Section: Role Of Sms In Bioremediationmentioning
confidence: 99%
“…This so-called phytostabilization results in the conversion of soluble heavy metals into insoluble compounds, for example by binding to organic matter (Wei et al 2020 ; Yu et al 2021 ). In addition, SMS of different mushroom forming fungi can degrade OMPs (Law et al 2003 ; Purnomo et al 2010 ; Sadiq et al 2018 ; Zang et al 2020 ) or stimulate OMP degrading bacteria in the soil (García-Delgado et al 2015 ; Wang et al 2016 ). In the case of waste water, SMS of A. bisporus was shown to reduce contamination by sorbing dyes and heavy metals (García-Delgado et al 2017 ; Toptas et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%